Effects of Lime and Concrete Waste on Vadose Zone Carbon Cycling. Issue 11 (17th November 2014) - Thaysen, E.M.; Jessen, S.; Postma, D.; Jakobsen, R.; Jacques, D.; Ambus, P.; Laloy, E.; Jakobsen, I.
Abstract : In a series of mesocosm experiments, with barley ( Hordeum vulgare L.) grown on podzolic soil material, we have investigated inorganic carbon cycling through the gaseous and liquid phases and how it is affected by different soil amendments. The mesocosm amendments comprised the addition of 0, 9.6, or 21.2 kg m −2 of crushed concrete waste (CCW) or 1 kg lime m −2 . The CCW and lime treatments increased the dissolved inorganic carbon (DIC) percolation flux by about 150 and 100%, respectively, compared to the controls. However, concurrent increases in the CO2 efflux to the atmosphere (ER) were more than one order of magnitude higher than increases in the DIC percolation flux. Analysis of soil solutions, coupled reactive‐transport modeling studies, and a decrease in soil carbonate contents over the experiment altogether suggested that the increased ER from amended mesocosms was derived from the carbonate contained in the amendments, which, hence, mostly escaped to the atmosphere. Our results are important in the context of climate change due to the widespread application of lime to acidic soils. The CCW amendment had no adverse effects on plant growth and groundwater quality.